2016
DOI: 10.1111/acem.13053
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for Hospitalization Among Emergency Department Patients With Syncope

Abstract: Cardiac syncope, particularly suspected arrhythmia, was the major reason for ED referrals and hospitalization. The majority of patients hospitalized for cardiac monitoring had no identified cause. An important number of patients suffered SAEs, particularly arrhythmias, outside the hospital. Development of a risk-stratification tool and out-of-hospital cardiac monitoring strategy should improve patient safety and save substantial resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Admission rates are quite variable from one provider, hospital, or region to another. 56 Admission rates in the US are approximately 32%, 53 while in Canada they are closer to 13%, 54 potentially due to differences in financial incentives, risk tolerance among clinicians, and availability of follow-up.…”
Section: Shared Decision-making For Moderate-risk Syncopementioning
confidence: 99%
“…Admission rates are quite variable from one provider, hospital, or region to another. 56 Admission rates in the US are approximately 32%, 53 while in Canada they are closer to 13%, 54 potentially due to differences in financial incentives, risk tolerance among clinicians, and availability of follow-up.…”
Section: Shared Decision-making For Moderate-risk Syncopementioning
confidence: 99%
“…9,[12][13][14][15] Associated hospital admission rates vary from 7.4 to 83%. 1,8,10,11,[16][17][18][19][20][21][22] Standard practice includes a detailed history, performing a physical examination, standard 12-lead electrocardiography (ECG) and orthostatic blood pressure measurement. The utility of other investigations, including cardiac biomarkers, is controversial, and evidence for routine laboratory investigations is currently lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The non-cardiac serious conditions are identified by thorough ED evaluation. It is the concern for occult arrhythmias that leads to hospitalisation for extensive investigations and monitoring 9. Over half of these hospitalisations are for suspected underlying arrhythmias.…”
Section: Introductionmentioning
confidence: 99%
“…Over half of these hospitalisations are for suspected underlying arrhythmias. A recently published study reported that of those patients admitted for suspected underlying arrhythmias, over 70% of patients are discharged from hospital with no cause of syncope ever found 9. To save resources and improve patient safety, ambulatory outpatient cardiac monitoring is a proposed alternative to inpatient cardiac monitoring 9…”
Section: Introductionmentioning
confidence: 99%